Semantic enrichment on large scanned collections through their "satellite texts": the paradigm of Migne's Patrologia Graeca. Issue 2 (16th August 2021) - Varthis, Evagelos; Tzanavaris, Spyros; Giarenis, Ilias; Papavlasopoulos, Sozon; Drakakis, Manolis; Poulos, Marios
Abstract : Purpose: This paper aims to present a methodology for the semantic enrichment on the scanned collection of Migne's Patrologia Graeca (PG), attempting to easily locate on the Web domain the scanned PG source, when a reference of this source is described and commented on another scanned or textual document, and to semantically enrich PG through related scanned or textual documents named "satellite texts" published by third people. The present enrichment of PG uses as satellite texts the Dorotheos Scholarios's Synoptic Index (DSSI) which act as metadata for PG. Design/methodology/approach: The methodology consists of two parts. The first part addresses the DSSI transcription via a proper web tool. The second part is divided into two subsections: the accomplishment of interlinking the printed column numbers of each scanned PG page with its actual filename, which is the build of a matching function, and the build of a web interface for PG, based on the generated Uniform Resource Identifiers (URIs) of the above first subsection. Findings: The result of the implemented methodology is a Web portal, capable of providing server-less search of topics with direct (single click) navigation to sources. The produced system is static, scalable, easy to be managed and requires minimal cost to be completed and maintained. The produced data sets of transcribed DSSI and the JavaScript Object Notation (JSON) matching functions are available for personal use of students and scholars under Creative Commons license (CC-BY-NC-SA). Social implications: Scholars or anyone interested in a particular subject can easily locate topics in PG and reference them, using URIs that are easy to remember. This fact contributes significantly to the related scientific dialogue. Originality/value: The methodology uses the transcribed satellite texts of DSSI, which act as metadata for PG, to semantically enrich PG collection. Furthermore, the built PG Web interface can be used by other satellite texts as a reference basis to further enrich PG, as it provides a direct identification of sources. The presented methodology is general and can be applied to any scanned collection using its own satellite texts.